Assessment of safe injection practices among healthcare workers in a tertiary care hospital - Sharma, H. C.; Dewan, Manasvee; Banerjee, Priyanka; Srivastava, Smriti; Sagar, Drishti; Yadav, Nisha (International Journal Of Community Medicine And Public Health, 2025)
Background: There is dearth of documented information about safe and unsafe injection practices in both developing and developed countries. Safe injection practices are intended to prevent transmission of infectious diseases from one patient to other, or between a patient and health care personnel during preparation and injection of medications. Documented record of the daily practices would lead to efficient monitoring. This will further enhance the prevention of infection by unsafe injection practices. Methods: It was cross-sectional study where healthcare workers (nursing staff, phlebotomists and doctors) were observed for safe injection practices in sample collection room, cath lab, wards and ICU. Healthcare workers were assessed by means of a pre-defined questionnaire where basic knowledge about the subject was assessed. Field training was given to the staff for safe injection practices. Results: While observing the different facilities, 28.57% had loose disposable needles lying outside packaging. 42.85% facilities had sharp waste lying in a container not meant for sharp waste. All sharp containers awaiting final disposal were stored in an area away from public access. Sharp container for final disposal in one of the facilities was not completely closed; its lid was open (14.28%). All the facilities had access to soap and water while 71% facilities had access to hand sanitizers. Pre and post tests showed the gaps in the knowledge of different healthcare workers which were improved by on-spot training. Conclusions: Education and training and regular audits go hand in hand in improving safe injection practices.